Co-modulation of TNFR1 and TNFR2 in an animal model of multiple sclerosis - Fiedler, Timon; Fairless, Richard; Pichi, Kira; Fischer, Roman; Richter, Fabian; Kontermann, Roland; Pfizenmaier, Klaus; Diem, Ricarda; Williams-Fairless, Sarah K. (Journal of neuroinflammation, 2023)
Tumour necrosis factor (TNF) is a pleiotropic cytokine and master regulator of the immune system. It acts through two receptors resulting in often opposing biological effects, which may explain the lack of therapeutic potential obtained so far in multiple sclerosis (MS) with non-receptor-specific anti-TNF therapeutics. Under neuroinflammatory conditions, such as MS, TNF receptor-1 (TNFR1) is believed to mediate the pro-inflammatory activities associated with TNF, whereas TNF receptor-2 (TNFR2) may instead induce anti-inflammatory effects as well as promote remyelination and neuroprotection. In this study, we have investigated the therapeutic potential of blocking TNFR1 whilst simultaneously stimulating TNFR2 in a mouse model of MS.